The Peace of God - Koziol, Geoffrey (Past imperfect (ARC Humanities Press), 2018)
The Peace of God was one of the most important movements of the Middle Ages, yet is highly contested. It has been seen as both radically innovative and fundamentally traditional; as millenarian and not millenarian; as a popular movement and as a way of consolidating power for the elites. Geoffrey Koziol argues for the validity of all these differing viewpoints, because specific instantiations of the Peace of God varied greatly, and there were inherent contradictions in early ideas of peace and peace-making.